PROVENANCE: An Intermediary-Free Solution for Digital Content Verification - Spillane, Brendan; Conlan, Owen (My University, 2021)
The threat posed by misinformation and disinformation is one of the defining challenges of the 21st century. Provenance is designed to help combat this threat by warning users when the content they are looking at may be misinformation or disinformation. It is also designed to improve media literacy among its users and ultimately reduce susceptibility to the threat among vulnerable groups within society. The Provenance browser plugin checks the content that users see on the Internet and social media and provides warnings in their browser or social media feed. Unlike similar plugins, which require human experts to provide evaluations and can only provide simple binary warnings, Provenance’s state of the art technology does not require human input and it analyses seven aspects of the content users see and provides warnings where necessary.
Fourth Workshop on Knowledge-driven Analytics and Systems Impacting Human Quality of Life (KDAH-CIKM-2021)
PUBLISHED
Gold Coast, Queensland, Australia
Keywords: Misinformation; Disinformation; Fake News; Social Media; Plugin; Browser Extension